2022
DOI: 10.3390/biomedicines10092292
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Tumor Vessels and Immune Cells Affects Immunotherapy of Glioblastoma

Abstract: Immunotherapies with immune checkpoint inhibitors or adoptive cell transfer have become powerful tools to treat cancer. These treatments act via overcoming or alleviating tumor-induced immunosuppression, thereby enabling effective tumor clearance. Glioblastoma (GBM) represents the most aggressive, primary brain tumor that remains refractory to the benefits of immunotherapy. The immunosuppressive immune tumor microenvironment (TME), genetic and cellular heterogeneity, and disorganized vasculature hinder drug de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…Aberrant vasculature is a hallmark of GBM pathology. The tumor vessels are collapsed and disorganized, which contributes to hypoxia and immunosuppression, and creates speci c TME (16, [41][42][43]. The astrocytes are displaced by glioblastoma, which disrupts the blood-brain barrier and results in a damaging 'permeability and retention effect' (44).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant vasculature is a hallmark of GBM pathology. The tumor vessels are collapsed and disorganized, which contributes to hypoxia and immunosuppression, and creates speci c TME (16, [41][42][43]. The astrocytes are displaced by glioblastoma, which disrupts the blood-brain barrier and results in a damaging 'permeability and retention effect' (44).…”
Section: Discussionmentioning
confidence: 99%
“…However, some GBM characteristics have been reported to hamper an effective influx of leucocytes. For example, reductions in the expression of intracellular adhesion molecule 1 (ICAM1) and vascular cell adhesion molecule 1 (VCAM1) at the BBTB may prevent leucocyte tethering and extravasation [ 48 ]. Furthermore, cytokines expressed by the CECs can create an immunosuppressive environment that hampers leucocyte activation and extravasation [ 49 , 50 ].…”
Section: Blood–brain Tumor Barrier and Drug Deliverymentioning
confidence: 99%
“…; Table 2, Ref. [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]). It has been reported that blocking the activity of IL-6R by tocilizumab in a glioma cell line (U87MG) prevented cell proliferation by acting through the Janus kinase/signal transducer and activator of transcription 3 (JAK/STAT3) pathways [25].…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%